Diversity and Spatial Distribution of Dung Beetles (Coleoptera: Scarabaeidae) in Two Habitat Types in West Sulawesi - Suparman Suparman; Muhammad Rizaldi Trias Jaya Putra Nurdin; Muhammad Mifta Fausan (Indonesian Journal of Ecology and Conservation, 2024)
Research on the diversity and spatial distribution of dung beetles in West Sulawesi remains limited, particularly across different habitat types. Dung beetles play important ecological roles as decomposers and bioindicators of environmental conditions. This study aimed to analyze the diversity and spatial distribution of dung beetles and their relationship with environmental parameters in two contrasting habitats: the montane forest of Gandang Dewata National Park, Mamasa Regency, and the lowland area of Baruga Barat, Majene Regency. Sampling was conducted using random plot sampling with flight intercept traps and pitfall traps. Environmental parameters measured included air temperature, humidity, light intensity, soil pH, and soil moisture. Data were analyzed using the Shannon–Wiener diversity index, dominance index, evenness index, similarity index, Morisita index, and Principal Component Analysis (PCA). A total of 66 individuals representing 10 species from two families and three genera were recorded. Eight species were found in Gandang Dewata National Park and four in Baruga Barat. The overall diversity index was moderate (H' = 1.549). The low similarity index (33%) indicates differences in species composition, while the Morisita index shows a clustered distribution pattern influenced by habitat conditions